OP0105 Long-term safety of tocilizumab from large clinical trial and postmarketing populations. (15th June 2017) - Mohan, S; Michalska, M; Yourish, J; Pei, J; Gale, S; Birchwood, C; Berber, E
Abstract : Background: Tocilizumab (TCZ) is a recombinant humanized monoclonal antibody targeted against the interleukin-6 receptor that was approved to treat rheumatoid arthritis (RA) in the EU in 2009 and in the US in 2010. TCZ has now completed long-term extension (LTE) follow-ups in a number of intravenous and subcutaneous RA trials. Objectives: To provide an updated report on the incidence of safety events during TCZ treatment in patients with RA using data from multiple completed clinical trials and their LTEs, as well as to provide an update from the global TCZ postmarketing safety database. Methods: Incidence and reporting rates of adverse events (AEs) of special interest, including infections, malignancies, anaphylaxis, bleeding events, myocardial infarctions, gastrointestinal perforations, strokes, hepatic events and demyelination, were estimated from 2 distinct patient data sets. Incidence rates were calculated from 12 completed TCZ RA clinical trials and their LTE periods and are reported as events per 100 patient-years (PY). Reporting rates were also estimated from the global TCZ postmarketing safety database (Oct 2008 to Oct 2015), which includes information from all spontaneously reported cases and non-interventional programs as well as literature cases, and are reported as cases per 100 patients. Results: The clinical trial all-exposure population consisted of 7647 TCZ-treated patients with RA (81.6% female; mean [SD] age, 52 [12.6] years), constituting 22, 394 PY (mean follow-up, 2.93 years) of exposure. The overall rate (95% CI) of serious AEs in the clinical trial population was 14.16 (13.67–14.66) per 100 PY. Overall incidence rates for individual events for the clinical trial population are reported in the Table and were consistent in each 6-month period over the 5-year duration. The global postmarketing population included 606, 937 patients. The overall spontaneous reporting rate (range) of AEs of special interest in the postmarketing population was 9.37 (7.35–10.56) cases per 100 patients. Reporting rates of individual safety events of interest in the global postmarketing population are shown in the Table and were consistent in each 6-month period over the 7-year duration. Conclusions: The safety profile of TCZ in the current analysis, which includes information about safety events from 12 clinical trials and their LTEs and across 7 years of real-world postmarketing reports encompassing $≈ $ 600, 000 patients, was consistent with previous safety reports. These findings are consistent with the previously reported profile of TCZ and indicate that there is no evidence of increased safety risk with increasing exposure to TCZ. Acknowledgements: This study was funded by F. Hoffmann-La Roche/Genentech, Inc. Disclosure of Interest: S. Mohan Employee of: Genentech, Inc., M. Michalska Employee of: Genentech, Inc., J. Yourish Employee of: Genentech, Inc., J. Pei Employee of: Genentech, Inc., S. Gale Employee of: Genentech, Inc., C. Birchwood Employee of: Genentech, Inc., E. Berber Employee of: Genentech, Inc.